Effect of isolated fatty acids from flaxseeds Linumusitatissimum against LeishmaniatropicaIn vitro. - Mohammed Hasan, Hasan (International Journal of Psychosocial Rehabilitation, 2021)
The current study aimed to test the effectiveness of Fatty acid separation from the seeds of the flax plant Linum usitatissimum on the parasite Leishmaniatropica. Palmatic acid, Steric acid, Olic acid, and Arachidic acid Behenic acid). These fatty acids were used as a possible anti-inflammatory agents in vitro, as the results showed that the concentration of 100 μg/ml gave a complete inhibition of the parasite’s growth in the promastigote form in 48 hours and up by 100% compared to the control group, which growth of the parasite was witnessed at all times, while the concentration of 25 μg/ml showed a decrease in the percentage of inhibition compared to the rest of the concentrations, which was 78.8% at the time of 96 hours, and the inhibitory concentration for 90% of the parasites (LC90) was at the concentration of 50 μg/ml. milliliters at log phase 96 hours of culture. This led to a reduction in the number of generations and an increase in the time required to produce them compared to the control group.